Plasma miR-153 and miR-223 Levels as Potential Biomarkers in Parkinson’s Disease - Wu, Li; Xu, Qian; Zhou, Mengxi; Chen, Yajing; Jiang, Chunyan; Jiang, Yuhan; Lin, Yin; He, Qing; Zhao, Lei; Dong, Yourong; Liu, Jianren; Chen, Wei (Frontiers in Neuroscience, 2022)
Background: Small molecule RNAs (miRNAs) could induce down-regulation of α-synuclein (SNCA) expression by binding the 3’ untranslated region of SNCA, thus playing an important role in the pathogenesis of Parkinson’s Disease (PD). Recent studies suggest that SNCA related miRNAs in saliva are promising PD biomarkers. Research on those miRNAs in plasma is rare in PD patients. Objective: To detect the plasma expression levels of three SNCA related miRNAs (miR-7, miR-153 and miR-223) in PD, and to explore their diagnostic value and associations with clinical phenotype. Methods: MiR-7, miR-153 and miR-223 levels were detected in plasma of 75 PD patients and 73 normal controls (NCs) via real-time quantitative polymerase chain reaction. The receiver operating characteristic (ROC) curves were delineated to evaluate their diagnostic value in PD. In addition, their associations with demographic, key motor and non-motor symptoms were explored by serial scales. Results: The expression levels of plasma miR-153 and miR-223 were significantly decreased in PD patients relative to NCs. The area under the ROC curve separating PD from NCs was 63.1% for miR-153 and 86.2% for miR-223, respectively. Plasma miR-153 level in de novo PD was lower than that in treated patients (p=0.006), its level increased gradually with disease duration (r=0.358, p=0.002) and Unified Parkinson’s Disease Rating Scale part III score (r=0.264, p=0.022). Plasma miR-223 level was decreased in patients with clinical probable rapid eye movement sleep behavior disorder (cpRBD) compared with those without cpRBD (p<0.001), and its level was negatively associated with RBD screen questionnaire score (r=-0.334, p=0.003). Multiple linear regression analysis revealed that disease duration(p=0.049) was the independent associated factor of miR-153 level; whereas, RBDSQ(p=0.009) was related to miR-223 level in PD. Conclusion: Plasma miR-153 and miR-223 level could be potential biomarkers of PD.